Two-dimensional bismuth vanadate photocatalytic nano material containing vanadium defects as well as preparation method and application of two-dimensional bismuth vanadate photocatalytic nano material
By introducing vanadium defects into BiVO4 and building a unique morphological structure, the problem of high photogenerated carrier recombination rate of BiVO4 photocatalyst is solved, its oxidation performance and photocatalytic activity are improved, and more effective elimination of water pollutants is achieved.
Patent Information
- Application Number
- CN202411762783.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-07
AI Technical Summary
The high photocatalyst recombination rate of BiVO4 photocatalysts limits its photocatalytic activity and makes it difficult to effectively separate and migrate photocatalytic carriers.
Vanadium defect was introduced into BiVO4, and a complexing effect with dodecyl trimethylammonium chloride at different hydrogen ion concentrations was created to construct a unique morphological structure, improving the separation and migration efficiency of photogenerated carriers.
By introducing vanadium defects, the recombination rate of photogenerated carriers is reduced, the oxidation performance and photocatalytic activity of BiVO4 are improved, and the elimination effect of water pollutants such as tetracycline is better.
Smart Images

Figure CN119565591A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of material preparation and water environment pollution remediation, and specifically relates to a two-dimensional bismuth vanadate photocatalytic nanomaterial containing vanadium defects, and a preparation method and application thereof. Background Art
[0002] With the continuous development of social economy, a large amount of waste caused by industrial production is discharged into the natural environment, and the harmful substances remaining in surface water have seriously threatened human health. Scientific researchers are committed to finding a green, environmentally friendly and sustainable new technology to deal with these difficulties. The use of sunlight to drive the photocatalytic decomposition of pollutants in water has aroused great interest as a strategy that can both solve environmental problems and be green and environmentally friendly. BiVO4 has the advantages of wide visible light absorption range, non-toxicity, strong stability and high valence band potential, and is widely used in the field of photocatalytic water pollution remediation. However, the high recombination rate of photogenerated carriers limits the further application of BiVO4. As one of the important factors affecting the activity of photocatalysts, how to improve the separation and migration efficiency of photogenerated carriers in BiVO4 has become the key to improving its photocatalytic activity. Summary of the invention
[0003] If defect energy levels are introduced into BiVO4 so that photogenerated carriers cannot directly recombine, the separation effect of photogenerated electrons and holes can be greatly improved, the number of photogenerated carriers participating in the photoredox reaction can be increased, and the oxidation performance of BiVO4 can be improved. The study found that the introduction of vanadium defects in BiVO4 and the construction of a unique morphological structure can be an effective strategy to improve the separation and migration efficiency of photogenerated carriers and enhance photocatalytic activity.
[0004] In order to solve the problem of low photocatalytic activity of BiVO4, the present invention utilizes the characteristic that dodecyltrimethylammonium chloride can produce different complexing effects with BiVO4 precursor ions at different hydrogen ion concentrations, and constructs vanadium defects inside BiVO4, thereby improving the separation of photogenerated electrons and holes and the oxidation ability of the catalyst, and ultimately enhancing its photocatalytic effect of eliminating tetracycline.
[0005] To achieve the above object, the technical solution adopted by the present invention is:
[0006] The present invention provides a method for preparing a two-dimensional bismuth vanadate photocatalytic nanomaterial containing vanadium defects, comprising the following steps:
[0007] The bismuth salt is dissolved in an acid solution, and sodium dodecylbenzene sulfonate is dissolved in the acid solution as a template agent to obtain a bismuth salt solution; preferably, the bismuth salt is bismuth nitrate pentahydrate, and the acid solution is dilute nitric acid.
[0008] Ammonium metavanadate and dodecyltrimethylammonium chloride are dissolved in an alkali solution to obtain an ammonium metavanadate solution; preferably, the alkali solution is a NaOH solution. The main reason is that sodium hydroxide has a large solubility, and OH- ion solutions of different concentrations can be prepared, and salt and water are formed after the reaction, which will not affect the experiment.
[0009] The ammonium metavanadate solution is slowly added dropwise to the bismuth salt solution to obtain a mixed solution, the pH value of the mixed solution is adjusted to 2-10, and then it is transferred to a reactor for hydrothermal reaction. After the reaction, the obtained precipitate is washed and dried to obtain a two-dimensional bismuth vanadate photocatalytic nanomaterial containing vanadium defects, which is marked as BiVO4-Vvs. Preferably, the pH value of the mixed solution is 5; the temperature of the hydrothermal reaction is 180-200°C (specifically 180°C, 190°C or 200°C, etc.), and the time is 90-150min (specifically 90min, 120min or 150min, etc.).
[0010] The present invention also provides the use of the above-mentioned two-dimensional bismuth vanadate photocatalytic nanomaterial containing vanadium defects in water pollution remediation. The material has a good elimination effect on water pollutants such as tetracycline.
[0011] The advantages and beneficial effects of the present invention are:
[0012] The preparation method of the two-dimensional bismuth vanadate photocatalytic nanomaterial containing vanadium defects provided by the present invention has the advantages of low cost, high efficiency, environmental friendliness, safety, convenience and simple process. The two-dimensional structure shortens the distance for photogenerated carriers to migrate to the catalyst surface, and improves the transfer efficiency of photogenerated carriers inside BiVO4-Vvs. After the introduction of vanadium defects, the recombination rate of photogenerated electrons and holes is greatly reduced, and the improvement of the photooxidation ability of BiVO4 is finally achieved. The two-dimensional bismuth vanadate photocatalytic nanomaterial containing vanadium defects prepared by the present invention has a good photocatalytic elimination effect on pollutants such as tetracycline, and has broad application prospects in the field of water pollution remediation. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 It is the XRD pattern of the product prepared in Example and Comparative Example;
[0014] Figure 2 It is the SEM picture of the product prepared by Example and Comparative Example;
[0015] Figure 3 It is the DRS diagram of the products prepared in Examples and Comparative Examples;
[0016] Figure 4 It is the result of the products prepared in the examples and comparative examples eliminating tetracycline under simulated sunlight;
[0017] Figure 5The photoluminescence spectra of BiVO4 and BiVO4-Vvs-5 excited at 350nm. DETAILED DESCRIPTION
[0018] The present invention is further described below in conjunction with the embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0019] In addition, unless otherwise specified, the preparation processes in the following examples are all conventional means in the prior art in the art, and therefore, they are not described in detail; the raw materials and reagents used are all commercially available products.
[0020] Example 1
[0021] A method for preparing a two-dimensional bismuth vanadate photocatalytic nanomaterial containing vanadium defects comprises the following steps:
[0022] First, weigh 1mmol of bismuth nitrate pentahydrate and 0.28mmol of sodium dodecylbenzene sulfonate and put them into 4mol / L dilute nitric acid and stir for 60min; weigh 1mmol of ammonium metavanadate and 0.3g of dodecyltrimethylammonium chloride, add them to 2mol / L NaOH solution, and stir for 60min to completely dissolve them. Then slowly add the ammonium metavanadate solution to the bismuth nitrate pentahydrate solution, adjust the pH value to 2, and stir for 60min. Then transfer the mixed solution to a polytetrafluoroethylene reactor and react at 200℃ for 120min. Finally, wash the obtained precipitate with deionized water 3-5 times, and then dry it at 60℃ for 10h. The obtained product is marked as BiVO4-Vvs-2.
[0023] Example 2
[0024] A method for preparing a two-dimensional bismuth vanadate photocatalytic nanomaterial containing vanadium defects comprises the following steps:
[0025] First, weigh 1mmol of bismuth nitrate pentahydrate and 0.28mmol of sodium dodecylbenzene sulfonate and put them into 4mol / L dilute nitric acid and stir for 60min; weigh 1mmol of ammonium metavanadate and 0.3g of dodecyltrimethylammonium chloride, add them to 2mol / L NaOH solution, and stir for 60min to completely dissolve them. Then slowly add the ammonium metavanadate solution to the bismuth nitrate pentahydrate solution, adjust the pH value to 5, and stir for 60min. Then transfer the mixed solution to a polytetrafluoroethylene reactor and react at 200℃ for 120min. Finally, wash the obtained precipitate with deionized water 3-5 times, and then dry it at 60℃ for 10h. The obtained product is marked as BiVO4-Vvs-5.
[0026] Example 3
[0027] A method for preparing a two-dimensional bismuth vanadate photocatalytic nanomaterial containing vanadium defects comprises the following steps:
[0028] First, weigh 1mmol of bismuth nitrate pentahydrate and 0.28mmol of sodium dodecylbenzene sulfonate and put them into 4mol / L dilute nitric acid and stir for 60min; weigh 1mmol of ammonium metavanadate and 0.3g of dodecyltrimethylammonium chloride, add them to 2mol / L NaOH solution, and stir for 60min to completely dissolve them. Then slowly add the ammonium metavanadate solution to the bismuth nitrate pentahydrate solution, adjust the pH value to 10, and stir for 60min. Then transfer the mixed solution to a polytetrafluoroethylene reactor and react at 200℃ for 120min. Finally, wash the obtained precipitate 3-5 times with deionized water, and then dry it at 60℃ for 10h. The obtained product is marked as BiVO4-Vvs-10.
[0029] Comparative Example 1
[0030] In order to facilitate experimental comparison, BiVO4 was synthesized according to the above conditions. The specific steps are as follows:
[0031] First, weigh 1mmol of bismuth nitrate pentahydrate and 0.28mmol of sodium dodecylbenzene sulfonate and put them into dilute nitric acid and stir for 60min; weigh 1mmol of ammonium metavanadate, add it to the NaOH solution, and stir for 60min to completely dissolve it. Then slowly add the ammonium metavanadate solution to the bismuth nitrate pentahydrate solution, adjust the pH value to 7, and stir for 60min. Then transfer the mixed solution to a polytetrafluoroethylene reactor and react at 200℃ for 120min. Finally, wash the obtained precipitate with deionized water 3-5 times, and then dry it at 60℃ for 10h to obtain the sample BiVO4.
[0032] Performance Testing
[0033] In order to verify and analyze the quality and catalytic performance of the BiVO4-Vvs photocatalytic material prepared by the present invention, the following characterization and performance tests were performed on the products prepared in the above embodiments and comparative examples:
[0034] Characterization of catalysts:
[0035] The XRD analysis of the samples was carried out using a Shimadzu XRD-6000 X-ray diffractometer, with a Cu target (λ=0.1541 nm), equipped with a graphite monochromator, a tube voltage of 40 KV, a tube current of 30 mA, a scanning speed of 5° / min, and a scanning angle range of 10-80°. The morphology of the samples was characterized by a QUANTA200 scanning electron microscope (SEM) (FEI Company, USA). The light absorption capacity and range of the photocatalyst were analyzed by UV-visible diffuse reflectance spectroscopy (DRS) on a UV-3600PLUS model. The photoluminescence (PL) spectrum was analyzed by an Edinburgh fluorescence spectrometer (FLS 980).
[0036] The products obtained in each embodiment and comparative example have the following characteristics: Figure 1-4 The specific analysis is as follows:
[0037] The X-ray powder diffraction analysis test results of the products prepared in each embodiment and comparative example are as follows: Figure 1 The X-ray diffraction (XRD) pattern of the prepared BiVO4-Vvs catalyst shows diffraction peaks at 19.0°, 28.7°, 30.6°, 34.5°, 35.2° and 39.9°, corresponding to the (001), (121), (040), (200), (002) and (211) crystal planes of the monoclinic phase, respectively. Figure 1 It can be seen that no diffraction peaks other than monoclinic BiVO4 were detected, which proves that the reaction between the precursors was very complete during the reaction.
[0038] The microstructures of different photocatalysts were observed by SEM characterization. Figure 2 Figure a in the middle shows that the pure phase BiVO4 has a two-dimensional nanosheet morphology. Figure 2 Figure b in the middle shows that BiVO4-Vvs-5 basically maintains the flake morphology of pure phase BiVO4, which is beneficial to shorten the distance for carriers to migrate to the surface of the material, thereby improving the photocatalytic activity of BiVO4. At the same time, it confirms that the introduction of defects does not destroy the microscopic morphology of the material. Figure 2 Figure c in the middle shows that the morphology of BiVO4-Vvs-2 is mainly block-like, mixed with some flake samples. Figure 2 Figure d shows that the morphology of BiVO4-Vvs-10 is large blocks. In order to prove the absence of vanadium, we analyzed the element content of BiVO4-Vvs-5 and BiVO4 by EDS characterization, and the results are listed in Table 1. As shown in Table 1, the atomic proportion of vanadium in the BiVO4-Vvs-5 sample is significantly smaller than that of pure phase BiVO4, indicating that vanadium defects have been successfully introduced.
[0039] Table 1 Element content analysis results of BiVO4-Vvs-5 and BiVO4
[0040]
[0041] Figure 3 This is the UV-Vis DRS spectrum. All BiVO4-Vvs samples in the figure show a wide visible light absorption range. The absorption band edge of BiVO4-Vvs-5 has a blue shift relative to pure BiVO4, which is caused by the increase in its valence band position, but the material basically maintains a strong visible light absorption ability.
[0042] The oxidative capacity of the prepared samples was tested by tetracycline elimination experiment. First, 100 mL of 20 mg·L -1 The aqueous solution of tetracycline was added to a 100mL sandwich beaker and stirred, and 5mL of the solution sample was taken out at the same time. Secondly, 0.1g of photocatalyst was added to the aqueous solution of tetracycline, stirred in the dark for 40 minutes to reach adsorption-desorption equilibrium, and then 5mL of the suspension was separated using a filter membrane. Finally, a 300W xenon lamp was used to irradiate the reaction system (equipped with a 420nm filter) and the water circulation cooling system was turned on. Every 20 minutes of irradiation, 5mL of the suspension was drawn with a syringe and filter membrane. The absorbance of tetracycline in the solution sample was measured at 357nm using a UV-visible spectrophotometer to evaluate the elimination effect of the catalyst on tetracycline. Figure 4 As shown in the figure, after 2 hours of visible light irradiation, the removal efficiency of tetracycline by 0.1g BiVO4 is 50.2%. After the introduction of vanadium defects, the elimination efficiency of tetracycline is improved. After 2 hours of visible light irradiation, BiVO4-Vvs-5 eliminates 81.0% of tetracycline. However, as the vanadium defect content continues to increase, the photocatalytic activity of BiVO4-Vvs decreases. This may be because too many vanadium defects hinder the flow of photogenerated electrons to the surface to participate in the photocatalytic reaction, thereby reducing the photocatalytic activity of the BiVO4-Vvs sample.
[0043] The separation and recombination behaviors of photogenerated electrons and holes in BiVO4 and BiVO4-Vvs-5 were studied by photoluminescence (PL) spectroscopy. Figure 5 The photoluminescence spectra of BiVO4 and BiVO4-Vvs-5 excited at 350nm are shown in Figure 2. The emission peak intensity of BiVO4-Vvs-5 is relatively weaker than that of BiVO4, indicating that its charge separation efficiency is higher. In summary, the carrier separation and migration of BiVO4-Vvs are improved after the introduction of vanadium defects.
[0044] Obviously, the described embodiments are only some embodiments of the present invention, but not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
Claims
1. A method for preparing a two-dimensional bismuth vanadate photocatalytic nanomaterial containing vanadium defects, characterized in that: The following steps are involved: dissolving a bismuth salt and a template agent in an acid solution to obtain a bismuth salt solution; dissolving ammonium metavanadate and dodecyltrimethylammonium chloride in an alkali solution to obtain an ammonium metavanadate solution; The ammonium metavanadate solution is added dropwise to the bismuth salt solution to obtain a mixed solution, and the pH value of the mixed solution is adjusted to 2-10, and then the mixed solution is transferred to a reactor for hydrothermal reaction. After the reaction is completed, the obtained precipitate is washed with water and dried to obtain the target product.
2. The method for preparing the two-dimensional bismuth vanadate photocatalytic nanomaterial containing vanadium defects according to claim 1, characterized in that: The bismuth salt is bismuth nitrate pentahydrate, and the acid solution is dilute nitric acid.
3. The method for preparing the two-dimensional bismuth vanadate photocatalytic nanomaterial containing vanadium defects according to claim 1, characterized in that: The template agent is sodium dodecylbenzene sulfonate.
4. The method for preparing the two-dimensional bismuth vanadate photocatalytic nanomaterial containing vanadium defects according to claim 1, characterized in that: The alkali solution is NaOH solution.
5. The method for preparing the two-dimensional bismuth vanadate photocatalytic nanomaterial containing vanadium defects according to claim 1, characterized in that: The pH value of the adjusted mixed solution is 5.
6. The method for preparing the two-dimensional bismuth vanadate photocatalytic nanomaterial containing vanadium defects according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 180-200° C. and the time is 90-150 min.
7. A two-dimensional bismuth vanadate photocatalytic nanomaterial containing vanadium defects, characterized in that: The invention discloses a novel nanostructured carbon foam prepared by the preparation method described in any one of claims 1 to 6.
8. Use of the two-dimensional bismuth vanadate photocatalytic nanomaterial containing vanadium defects as claimed in claim 7 in water pollution remediation.
9. The use of the two-dimensional bismuth vanadate photocatalytic nanomaterial containing vanadium defects in water pollution remediation according to claim 8, characterized in that: The contaminant is tetracycline.